2009
DOI: 10.1016/j.otohns.2008.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Histologic analysis of the effects of three different support materials within rat middle ear

Abstract: Compared with gelfoam, both sepragel and nasopore caused less histologic alterations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 18 publications
4
36
1
Order By: Relevance
“…In the present study, macrophages showed the greatest recruitment in general with less B-cells and with very few T-cells engaged, indicating that the healing process differ when Gelfoam 1 /G-CSF is introduced, compared to open perforations [14]. This is in agreement with other reports where Gelfoam 1 is shown to give a more severe inflammatory reaction than other supporting materials [19]. However, infected ears are shown to regenerate faster than non-infected ones when a myringotomy is performed, probably functioning as a stimulating agent [20].…”
Section: Gelfoam 1 As a Supporting Matrixsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, macrophages showed the greatest recruitment in general with less B-cells and with very few T-cells engaged, indicating that the healing process differ when Gelfoam 1 /G-CSF is introduced, compared to open perforations [14]. This is in agreement with other reports where Gelfoam 1 is shown to give a more severe inflammatory reaction than other supporting materials [19]. However, infected ears are shown to regenerate faster than non-infected ones when a myringotomy is performed, probably functioning as a stimulating agent [20].…”
Section: Gelfoam 1 As a Supporting Matrixsupporting
confidence: 92%
“…After application of Gelfoam 1 an infiltration of neutrophils, fibroblasts and an angiogenesis have been described in the surrounding tissue and matrix [19]. In the present study these results could not be supported except for in the Gelfoam 1 itself, which might be due to the short observation time.…”
Section: Gelfoam 1 As a Supporting Matrixcontrasting
confidence: 90%
See 1 more Smart Citation
“…The safety of OTO-104, and hence its vehicle poloxamer 407, is in sharp contrast to the deleterious effects observed for several other polymers administered intratympanically. For instance, middle ears of rats treated with a gelatin matrix (Gelfoam) revealed a severe acute inflammatory response leading to prominent tissue fibrosis within 2 to 3 weeks of treatment (25). A hyaluronic acid polymer (Sepragel), although highly biocompatible, caused mild inflammatory reaction and fibrosis in the middle ear (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9] Although we found some animal studies in literature evaluating biocompatibility of spongostan, merocell, and ventilation tube used in ear-nose-throat surgeries and investigating whether they have any negative effects on the success rate of surgery, we could not find any cytotoxicity studies carried out with cell culture and 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT test) test. [10][11][12][13] The MTT test is widely used in the assessment of drugs and chemicals, but is less well accepted in the study of toxicity of AbstrAct Purpose: The aim of this study was to determine biocompatibility of spongostan, merocell, and ventilation tube using agar diffusion and 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide tests in cell culture and to evaluate the results in terms of clinical practices. Materials and Methods: The experimental procedures involved in this study were approved by the Animal Ethics Committee of Cumhuriyet University (B.30.2.CUM.0.01.00-50/4), and the study was conducted following accepted guidelines for the care and use of laboratory animals for research.…”
mentioning
confidence: 99%